Design of a Small Wind Turbine Emulator for Testing Power Converters Using dSPACE 1104 - Boutabba, T.; Benlaloui, Idriss; Mechnane, F.; Elzein, I. M.; Ma'arif, Alfian; Hassan, Ammar M.; Mahmoud, Mohamed Metwally (International Journal of Robotics and Control Systems, 2025)
Interest in wind turbine emulators (WTE) has increased due to the growing need for wind power generation as a low-maintenance, more effective substitute for conventional models. This paper presents the design of a small WTE utilizing a dSPACE 1104 system. The setup includes a DC motor, driven by a buck converter, coupled to a permanent magnet synchronous generator, all managed through a hardware-in-the-loop configuration using the dSPACE 1104 board. The DC motor simulates the rotational motion generated by wind energy, accurately replicating the characteristics of an actual WT. This control system enables the simulation of various wind speeds and torque values in MATLAB/Simulink software, providing a valuable tool for analyzing and developing power converters. The results obtained confirmed the effectiveness of the proposed emulator, as the experimental outcomes closely matched the theoretical calculations.